Safinamide in the management of patients with Parkinson’s disease not stabilized on levodopa: a review of the current clinical evidence - Bette S; Shpiner DS; Singer C; Moore H (Dove Medical Press, 2018)
Sagari Bette, Danielle S Shpiner, Carlos Singer, Henry Moore Department of Neurology, Division of Parkinson’s Disease and Movement Disorders, University of Miami – Miller School of Medicine, Miami, FL, USA Abstract: Safinamide (Xadago®) is a novel medication with both dopaminergic and non-dopaminergic effects, approved first by the European Commission and more recently by the US Food and Drug Administration (FDA) as an adjunctive treatment to carbidopa/levodopa in patients with mid- to late-stage Parkinson’s disease (PD) and motor fluctuations. It works through multiple mechanisms, namely as a reversible selective monoamine oxidase-B inhibitor and through modulation of glutamate release. Safinamide is extensively metabolized via oxidation to several inactive metabolites that are excreted primarily through the urine. Several large Phase III clinical trials of patients with advanced PD with motor fluctuations have shown that safinamide, administered orally at doses of 50–100 mg daily, increased ON time with no or non-troublesome dyskinesia, decreased daily OFF time, improved overall motor function (as measured by Unified Parkinson’s Disease Rating Scale [UPDRS] part III total score), and quality of life (as measured by Clinical Global Impression-Change and 39-item Parkinson’s Disease Questionnaire). In large clinical trials of patients with early PD on a single dopamine agonist, safinamide administered orally at a dose of 100 mg daily improved overall motor function as measured by UPDRS part III total score; however, some of the results reported were exploratory. Safinamide is generally well-tolerated and safe, with few to no treatment-related adverse events. Safinamide does not cause new or worsening dyskinesia and may be able to reduce this symptom in patients reporting it at baseline. Evidence suggests that safinamide is a good option for add-on therapy to carbidopa/levodopa in patients with advanced PD with motor complications, but there is still insufficient evidence to recommend it as monotherapy or add-on therapy in patients with early PD. Keywords: Parkinson’s disease, safinamide, MAO-B inhibitor, motor fluctuations, dyskinesia